Evaluación de la calidad del aire mediante material particulado pm2,5 y pm10 en la parroquia la Victoria, cantón Pujilí, provincia de Cotopaxi, periodo 2019 – 2020. - Jiménez Quispe, Erika Johana (2020)
There are various elements that contribute to the increasing pollution of the atmosphere, one of them is particulate matter (PM), a material of natural and anthropogenic origin, which, due to its small size, causes the degradation of air quality, damage to infrastructure, generates harmful effects on plants, animals and human health, especially the respiratory system. Therefore, the main purpose of the present research study was to determine the concentrations of PM (PM10 and PM2.5) in "La Victoria" Parish located in Pujilí Canton, two points were identified in the area where the sampling was carried out. The first sampling was carried out in the 'Centro sector' and the second one in 'Mulinliví Centro' neighborhood. The equipment used in the monitoring process was a portable beta attenuation monitor (E-BAM). The measurements were performed for a period of 24 continuous hours for both PM2.5 and PM10 at each selected point. The arithmetic means of the data recorded by the team at both sites were compared with the maximum concentration values for PM10 and PM2.5 established by the environmental regulations in force in the country. The figures resulting from the monitoring process indicated that they are below the maximum permitted concentration limits. However, there were specific hours where the concentrations of both particles increased. Therefore, it was essential to establish preventive actions to control particulate pollution in the research area.